Population Pattern of Pneumococci with Lower Susceptibility to Penicillin and Prospects of Antipneumococcal Vaccination to Control Antibiotic Resistance Distribution - S. V. Sidorenko; T. A. Savinova; E. N. Ilyina; M. A. Syrochkina (Антибиотики и Химиотерапия, 2020)
Large-scale antipneumococcal vaccination is followed by changes in the serotype composition and level of antibiotic resistance in pneumococci. The aim of the study was to evaluate the serotype composition and population pattern of pneumococci with lower susceptibility to penicillin before large-scale antipneumococcal vaccination. Among 260 Streptococcus pneumoniae strains isolated in the Russian Federation within 2003-2007, serotypes 23F (37.2%) and 19F (13.9%) were the most frequent ones. 19.3% of the isolates belonged to serogroup 6, 3.6% of the isolates each belonged to serotype 3 and serogroup 18, 4.9% of the isolates belonged to serotype 14 and 2.2% of the isolates belonged to serotype 19A. 66.8% of the isolates belonged to serotypes of the 7-valent conjugated pneumococcal vaccine, 67.3 and 82.1% of the isolates belonged to the 10- and 13-valent conjugated pneumococcal vaccines respectively. The isolates with lower susceptibility to penicillin were characterized by significant clonality and 56.9% of them belonged to 4 global clonal complexes (CC81, CC156, CC320 and CC315). Inclusion of the conjugated antipneumococcal vaccine to the National Vaccination Time-Table of the Russian Federation could promote lower levels of antibiotic resistance in pneumococci.